2018
DOI: 10.1021/acs.est.8b00829
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Distribution of Novel Perfluoroether Carboxylic and Sulfonic Acids in Surface Water

Abstract: Driven by increasingly stringent restrictions on long-chain per- and polyfluoroalkyl substances (PFASs), novel fluorinated compounds have emerged on the market. Here we report on the occurrences of several perfluoroalkyl ether carboxylic and sulfonic acids (PFECAs and PFESAs), including hexafluoropropylene oxide dimer and trimer acids (HFPO-DA and HFPO-TA), ammonium 4,8-dioxa-3 H-perfluorononanoate (ADONA), chlorinated polyfluorinated ether sulfonic acid (6:2 Cl-PFESA), and its hydrogen-substituted analogue (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
242
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(251 citation statements)
references
References 27 publications
6
242
3
Order By: Relevance
“…We observed a median dissolved PFOS concentration in surface water of 1.1 ng L -1 (mean = 1.04 ± 0.33 ng L -1 , range: 0.48-1.6 ng L -1 ), a relatively low level compared to some major hydrosystems worldwide (Pan et al, 2018). The median PFOS level in the present survey is also about 20 times lower than that in the Seine River downtown Paris (Labadie and Chevreuil, 2011b).…”
Section: Seasonal Variations Of Pfas Levels and Profiles In The Watercontrasting
confidence: 55%
“…We observed a median dissolved PFOS concentration in surface water of 1.1 ng L -1 (mean = 1.04 ± 0.33 ng L -1 , range: 0.48-1.6 ng L -1 ), a relatively low level compared to some major hydrosystems worldwide (Pan et al, 2018). The median PFOS level in the present survey is also about 20 times lower than that in the Seine River downtown Paris (Labadie and Chevreuil, 2011b).…”
Section: Seasonal Variations Of Pfas Levels and Profiles In The Watercontrasting
confidence: 55%
“…Based on their structurally inherent thermal and chemical stability, PFAS persist in the environment where they are generally resistant to biodegradation, photooxidation, direct photolysis, and hydrolysis (Schultz et al 2003). As a result, they are widely detected in the environment (Dauchy et al 2019;Pan et al 2018), wildlife (Cui et al 2018;Escoruela et al 2018;Route et al 2014), drinking water (Guelfo and Adamson 2018;, and humans (Daly et al 2018;Hurley et al 2018;Jain 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative chemistries that retain the long-chain character, such as ADONA, were engineered with ether linkages and sites of hydrogenation in efforts to reduce biological half-lives (Fromme et al 2017). Replacement PFAS are therefore increasingly detected in the environment, including in surface water (De Silva et al 2011;McCord et al 2018;Pan et al 2018;Strynar et al 2015;Wang et al 2016) and drinking water (Kaboré et al 2018;McCord et al 2018). Environmental screening efforts have also identified relevant exposures to PFAS by-products, such as sulfonated fluorovinyl ethers (i.e., PFESA compounds), that are not strictly chemicals of commerce (McCord et al 2018;Strynar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PFASs in the Nordic environment (Pan et al, 2018), and reported a median concentration of 0.95 ng/L in 160 samples from China, Korea, Sweden, US and UK, which demonstrates that HFPO-DA distribution is ubiquitous. However important information regarding its annual production volume, emission sources and toxicity remains unclear.…”
mentioning
confidence: 97%